Optimizing Event Marketing Strategies in Increasing Brand Awareness at Ichigo Daifuku Surabaya - Nabilla Rahma Maharsany; Yanda Bara Kusuma (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to identify the event marketing strategies used to increase brand awareness at Ichigo Daifuku Surabaya. The research adopts a descriptive qualitative method and was conducted at Ichigo Daifuku Surabaya, which operates three outlets in and around Surabaya. The subjects of this research include the owner, employees, and customers of Ichigo Daifuku Surabaya. Data were collected using interviews, observation, documentation, and triangulation techniques. The data analysis process involved data reduction, data display, and drawing conclusions. The results of the study indicate that Ichigo Daifuku Surabaya implements event marketing strategies through the selection of strategic event locations, choosing relevant event vendors, and engaging directly with consumers. The company also optimizes its strategies by actively participating in events, using social media as a promotional support tool, and creating memorable experiences for customers. These strategies have proven effective in enhancing brand awareness and customer loyalty.